THE ROLE OF INTERDISCIPLINARY METHODOLOGY IN THE STUDY OF SOCIALLY HAZARDOUS BEHAVIOR (World Conference on Social Sciences, Law and Public Policy, 2026)
Under the conditions of the transformation of modern social sciences and humanities, the fundamental and objective study of complex social phenomena-specifically socially hazardous (risky), destructive, and deviant behavioral patterns—through monodisciplinary paradigms demonstrates its methodological limitations. Amid the increasing complexity of human actions, digitalization, and global social anomie, hazardous behavior manifests not merely as an individual psychological deviation, but as an integral outcome of socio-institutional crises and the erosion of existential-ethical values. To comprehend the essence of this phenomenon and formulate preventive mechanisms, adopting an interdisciplinary approach grounded in the synergistic collaboration of psychological, sociological, and philosophical methodologies becomes strategically imperative. Interdisciplinary methodology enables the synthesis of intrapsychic dynamics, socio-structural factors, and fundamental ontological-axiological foundations of deviance into a unified methodological system. Evaluating the multifaceted consequences of hazardous behavior necessitates extending analysis beyond traditional micro- and macroeconomic indicators to encompass spatial, neuro-sociological, and institutional-dynamic paradigms. Ultimately, interdisciplinary integration serves as a foundational framework for developing holistic state preventive policies that combine social-institutional reforms, psychological rehabilitation, and the restoration of moral-axiological environments.
Keywords: Socially hazardous behavior, interdisciplinary methodology, anomie, existential vacuum, social capital, normalization of deviance, spatial deviance, neuro-sociology, biopolitics.